Analysis of Risk Factors on Patellofemoral Osteoarthritis: Distribution Characteristics and Radiographic Parameters of Patellofemoral Joint - Jianlin Zhao; Jinsong Liu; Jing Han; Xiaoyu Wan; Wenqian Xu; Zengrui Zhang; Yingxing Xu (Orthopaedic Surgery)
ABSTRACT Objective The risk factors for the degeneration of the patellofemoral joint (PFJ) have not been adequately and thoroughly studied. This study aimed to analyze the population distribution characteristics of patients with patellofemoral osteoarthritis (PFOA) and assess the correlation between PFOA and radiological parameters, including patella morphology, PFJ congruity, and patellar alignment. Moreover, the risk factors across various demographic groups were further analyzed. Methods A retrospective analysis was conducted to examine the population distribution characteristics of PFOA patients from September 2020 to September 2023. Radiological parameters of the PFJ were measured from the anteroposterior and lateral views of knee joint as well as axial view of patella using X‐ray imaging and the PACS imaging system at the First Affiliated Hospital of Kunming Medical University. These parameters included patella morphology (patella type, width, thickness, and Wiberg index), PFJ congruity (patella height, Wiberg angle, sulcus angle, and lateral patella angle), and patellofemoral alignment (patella tilt angle, displacement, and lateral patellofemoral angle). PFOA severity was classified according to the Iwano PFJ radiological classification, and its correlation with the aforementioned parameters was examined. Additionally, risk factors for PFOA across different populations were further evaluated. Results The study included 1080 patients according to the inclusion and exclusion criteria. Age, female gender, overweight or obesity, and manual workers were significantly associated with PFOA. Moreover, type III patella (OR = 3.03, p < 0.05), greater patella width (OR = 1.12, p = 0.01), sulcus angle (OR = 1.04, p < 0.01), patella tilt angle (OR = 1.13, p < 0.01), and patella displacement (OR = 1.22, p < 0.01) as well as smaller patella thickness (OR = 0.87, p < 0.01), Insall–Salvati index (OR = 0.24, p = 0.04), and lateral patellofemoral angle (OR = 0.93, p = 0.02) were identified as risk factors for PFOA. Furthermore, greater patella thickness (OR = 1.17, p < 0.05) and smaller patella displacement (OR = 0.79, p < 0.01) correlated with higher Kujala patellofemoral scores. Discrepancies in risk factors across different populations were also observed. Conclusions Older age, female gender, obesity, manual workers, and specific aberrations in patellofemoral parameters are predictive factors for PFOA. Additionally, greater patella thickness and smaller patella displacement were associated with increased severity of clinical symptoms. Thus, more attention should be paid to the discrepancies that exist in different populations.